Comparison of self-adhering flowable composite microleakage with several types of bonding agent in class V cavity restoration - Atefeh Yousefi Jordehi; Maryam Shakur Shahabi; Alireza Akbari (Wolters Kluwer Medknow Publications, 2019)
Background: The aim of the present study was to compare the marginal seal of self-adhering flowable composite resin with three universal bonding systems using the self-etch technique in Cl V cavities at enamel and dentin margins. Materials and Methods: In this in vitro study, Cl V cavities were prepared on the buccal surfaces of forty premolars, with the occlusal margin of each cavity on enamel and gingival margin on dentin. The teeth were divided into four groups (n = 10) in terms of the adhesive used; Group 1: Vertise Flow (VF) self-adhering composite resin, Group 2: Clearfil S3 Bond Universal (CS3BU), Group 3: G-Premio Bond (GPB), Group 4: Single Bond Universal (SBU). In Groups 2, 3, and 4, Z350 flowable composite resin was used to restore the cavities. After thermocycling, the samples were immersed in 10% methylene blue for 24 h and evaluated under a stereomicroscope after buccolingual sectioning; microleakage at enamel and dentin margins was recorded. Kruskal-Wallis and Mann-Whitney tests were used for statistical analyses. Statistical significance was set at P < 0.5. Results: Vertis Flow self-adhering composite resin exhibited significantly higher microleakage at enamel and dentin margins compared to SBU and CS3BU; however, it had significantly less microleakage at enamel margin compared to GPB (P < 0.05). At the enamel and dentin margins, the minimum microleakage values were recorded at SBU and CS3BU margins, respectively. GPB exhibited the highest microleakage values among the groups evaluated and in all the groups, microleakage at dentin and enamel margins was significantly different (P < 0.05) except for SBU group. Conclusion: The marginal sealing ability of self-adhering flowable composite resin at enamel and dentin margins was poor compared to the majority of bonding agents evaluated.